1997
DOI: 10.1055/s-2006-957733
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Cytokine-Stimulating Activities of Acidic Heteroglycans fromTremella fuciformis

Abstract: Four acidic heteroglycans, T2a-T2d, were isolated from the body of Tremella fuciformis Berk. They contained 1.9%-2.9% of acetyl groups and were composed of mannose (Man), glucuronic acid (GlcA), and small amounts of xylose (Xyl), glucose (Glc), and fucose (Fuc). According to methylation analysis they had a mannan backbone consisting of 3-linked Man, and side chains containing glucosyl, mannosyl, fucosyl, xylosyl, and glucuronic acid residues. The side chains were attached through O-2, O-4, or O-6 in about 40 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 6 publications
1
19
1
Order By: Relevance
“…The ash content of TAU, TFO, TIN and TEN (Table 1) was found to be higher compared to other polysaccharides. The ash content found in this study was higher (3.37%) in the polymer isolated from T. fuciformis compared to the reported value 0.4% (Gao et al, 1997). However, the ash content of all Tremella polysaccharides was much lower than other commercially available extra-cellular polysaccharides, e.g.…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…The ash content of TAU, TFO, TIN and TEN (Table 1) was found to be higher compared to other polysaccharides. The ash content found in this study was higher (3.37%) in the polymer isolated from T. fuciformis compared to the reported value 0.4% (Gao et al, 1997). However, the ash content of all Tremella polysaccharides was much lower than other commercially available extra-cellular polysaccharides, e.g.…”
Section: Resultscontrasting
confidence: 85%
“…A small amount of fucose and ribose was present in some of the species (Table 2). Previous researchers have isolated neutral and acidic heteroglycans from the fruiting bodies of T. fuciformis (Gao et al, 1996a, 1996b, 1997; Yui et al, 1995). They also reported some additional carbohydrates in the heteropolysaccharides of the fruiting bodies of T. fuciformis , such as fucose (Gao et al, 1996a, 1996b), xylobiose (Yui et al, 1995), fructose and glucose (Zhang and Hong, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the medicinal extracts from mushrooms are different forms of polysaccharides and all of them are strengtheners of the immune system with little or no side effects (Oei, 1991(Oei, , 1996Gao et al, 1997). For example, a sizofiran, antitumour polysaccharide extracted from the culture broth of Schizophyllum commune is an effective immuno-therapeutic agent for cervical carcinoma because it stimulates a rapid recovery of the immunological status impaired by radiotherapy (Miyazaki et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Some mushrooms such as Tremella fulciformis are used for curing leukaemia, coughing, phlegm and asthma of patients suffering from chronic bronchitis (Oei, 1991(Oei, , 1996. According to Gao et al (1997) mushrooms like T. fulciformis also possesses antitumour, hypoglycaemic and cytosine stimulating activities. Antinoceptive components have been isolated from Ganoderma lucidum (Koyama et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (2008) demonstrated that chemical str ucture of the polysaccharides consists of a linear backbone of (1→3) α-D-mannan (with side chains composed of glucuronic acid, xylose and fucose) backbone chain to which β-(1→2)-linked D-xylose residues are attached at the C-2 position. The estimated ratio of mannose, fucose, xylose, and glucuronic acid is 9:1:4:3 that makes glucoronic acid accounted for 17.6% of the polysaccharides content in T. fuciformis (De Baets and Vandamme, 2001;Gao et al, 1996Gao et al, , 1997Tsing, 2006;Wu et al, 2008;Kakuta et al, 1979;Khondkar, 2009).…”
Section: Analysis Of Tremella Fuciformismentioning
confidence: 99%